Implementing Blended Learning in Teaching English at Higher Education in Industrial Revolution 4.0 - Dian Anggraini (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
This research aims to find the effect of blended learning toward student’s achievement at higher education. This strategy is expected to contribute to be better in teaching at UPI “yptk” Padang. The research is an experiment which population consists of the students academic year of 2018/2019. Instrument is used in collecting data of this research was treatment materials in the form of blending learning and data collection instruments. The results of this research revealed a significant influence on the students’ achievement.